Optimization of Customer Service Quality Using ISO 9001:2015 Principles at PT. Trust Pearl - Muhammad Fendy Pradana; Mohammad Yaskun; Evi Fijrotun (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This study aims to analyze the quality of services provided by PT. Mutiara Amanah to its customers (Umrah pilgrims) based on the dimension of service quality, and to formulate an ISO 9001:2015 implementation strategy to improve service quality. The qualitative descriptive method was used with data collected through in-depth interviews using pattern matching analysis, observations, document studies, and Focus Group Discussions (FGD) with the PDCA (Plan-Do-Check-Act) approach. This research was conducted from August to October 2022 at PT. Mutiara Amanah, Bojonegoro. The results showed that the company's service quality met the five dimensions of SERVQUAL: reliability, responsiveness, assurance, empathy, and tangible appearance, achieving a satisfaction score of 81% from 50 respondents. The FGD identified 140 complaints from pilgrims and 140 service desires, which were then reduced to five main categories. Using Pareto analysis, 80% of complaints come from 20% of service areas, with external services (airlines, hotels, visa providers) and personal services as the main concerns. The company's ISO 9001:2015 implementation strategy includes the PDCA cycle: planning, complaint identification, implementation of service improvements, checking through the Tour Guide handbook, and action by updating SOPs. These findings show that the PDCA-based ISO 9001:2015 framework is effective in systematically improving the quality of Umrah travel services.